2003
DOI: 10.1007/s00467-003-1157-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and metabolic determinants of increased plasma plasminogen activator inhibitor-1 activity in children with renal transplants

Abstract: Recent studies have shown that activity of plasminogen activator inhibitor-1 (PAI-1), a prothrombotic protein, may be increased in transplanted patients. The aim of the present investigation was to determine PAI-1 activity in pediatric recipients of renal transplants and to establish the relative contribution of both genetic and metabolic factors. In 29 children and adolescents with stable renal transplants, we related plasma PAI-1 activity to an indicator of inflammatory status [plasma concentration of C-reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…Increased plasma PAI-1 activity, inflammatory status, as judged by values of plasma CRP, and insulin resistance are independent but closely related markers of atherogenesis [29,30,31,32]. In this same group of transplanted patients we found that plasma PAI-1 activity was significantly elevated and correlated positively with CRP, fasting insulinemia, and the HOMA index [4]. The finding in the present study of an association between plasma PAI-1 activity and total fat intake was expected [33].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Increased plasma PAI-1 activity, inflammatory status, as judged by values of plasma CRP, and insulin resistance are independent but closely related markers of atherogenesis [29,30,31,32]. In this same group of transplanted patients we found that plasma PAI-1 activity was significantly elevated and correlated positively with CRP, fasting insulinemia, and the HOMA index [4]. The finding in the present study of an association between plasma PAI-1 activity and total fat intake was expected [33].…”
Section: Discussionsupporting
confidence: 55%
“…The data depicted in Table 2 have been reported previously [3,4]. A number of transplanted children had a cluster of risk factors predisposing to cardiovascular disease: high plasma levels of triglycerides, total cholesterol, and low-density lipoprotein (LDL)-cholesterol, insulin resistance, hyperhomocysteinemia, high plasma PAI-1 activity, and elevated CRP.…”
Section: Plasma Biochemical Profilementioning
confidence: 92%
See 2 more Smart Citations
“…This risk persists after renal transplantation because of many factors such as hypertension, dyslipidemia, hyperhomocysteinemia, hyperparathyroidism, obesity, insulin resistance, posttransplant diabetes, and immunosuppressive therapy, among others (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%